Defining and measuring informality in the Turkish labor market - Elif Öznur Acar; Aysıt Tansel (Turkish Economic Association, 2014)
This paper investigates how informality can be defined and measured in the Turkish labor market. Two alternative definitions of informality are used to explore their relevance and implications for the Turkish labor market using descriptive statistics. They are the enterprise definition and the social security definition. Further, contributions of individual and job characteristics to the likelihood of informality are investigated using multivariate probit analysis under the two definitions. The social security registration criterion is found to be a better measure of informality in the Turkish labor market given its ability to capture the key relationships between several individual and employment characteristics and the likelihood of informality.The study suggests that preference should be given to social security definition of labor informality for a more accurate depiction of the Turkish labor market. The suitability of the two alternative definitions of informality in the Turkish labor market and its implications have not been investigated before.
Keywords: J20; J21; J24; O17; 330; Informality; Definition; Measurement and Likelihood; Turkey